FastFabric: Scaling hyperledger fabric to 20 000 transactions per second. Issue 5 (11th February 2020) - Gorenflo, Christian; Lee, Stephen; Golab, Lukasz; Keshav, Srinivasan
Summary: Blockchain technologies are expected to make a significant impact on a variety of industries. However, one issue holding them back is their limited transaction throughput, especially compared to established solutions such as distributed database systems. In this paper, we rearchitect a modern permissioned blockchain system, Hyperledger Fabric, to increase transaction throughput from 3000 to 20 000 transactions per second. We focus on performance bottlenecks beyond the consensus mechanism, and we propose architectural changes that reduce computation and I/O overhead during transaction ordering and validation to greatly improve throughput. Notably, our optimizations are fully plug‐and‐play and do not require any interface changes to Hyperledger Fabric. Abstract : This work shows how a permissioned blockchain framework such as Hyperledger Fabric can be re‐engineered to support nearly 20 000 transactions per second, a factor of almost 7 better than the prior work. We accomplished this goal by implementing a series of independent optimizations focusing on I/O, caching, parallelism and efficient data access. We also use aggressive caching, and we leverage lightweight data structures for fast data access on the critical path.